Some Issues of Middle-Class Formation in the Republic of Armenia - Markosyan, Ashot; Markosyan, Meruzhan («Տնտեսագետ» հրատ․)
A stable and fair society is formed and established based on the principle of fair distribution of incomes and expenses of the population, the implementation of which is the core and main direction of social policy. Although any society can be conventionally divided into "poor", "middle" and "rich" groups, for the establishment of a just state, it is important to distribute income and expenses among the mentioned groups in such a way that the minimum share of the "poor" group is ensured, as well as the formation of the middle group at the most and the creation of a "rich" group whose incomes only marginally exceed the incomes or consumption levels of the "poor" group. Social policy is considered successful if the middle class prevails among the three groups mentioned above. Accordingly, the establishment of the middle class is not only of political, social, and economic importance, but it is also the "cement" that completes and unites the progress of the society and the state. The purpose of the article is to identify the problems of the formation of the middle class in the Republic of Armenia and to point out the main ways of its establishment. To achieve that goal, the following issues were put forward by: • investigating the identification of population income and consumption expenditure patterns by quintile groups and disparities, • emphasizing the social significance of poverty reduction, by limiting the incomes of the rich classes of the population, based on the consideration that the effect of these restrictions should be directed to increase the incomes and consumption of the middle class.
Keywords: Social policy